The role of melatonin in prevention of intestinal ischemia-reperfusion injury in rats - Kazez, A; Demirbag, M; Üstündag, B; Özercan, IH; Saglam, M (W B Saunders Co-Elsevier Inc, 2000)
Background/Purpose: The aim of this study was to determine the effect of melatonin, a hormone that is known as an antioxidant, on the prevention of tissue damage during mesenteric ischemia/reperfusion (I/R). Methods: A total of 40 young Wistar-al bi no rats were divided equally into 4 groups with varied treatment. Group 1 was control (sham), group 2 was I/R, group 3 was I/R plus melatonin (10 mg/kg) and group 4 was I/R plus melatonin (20 mg/kg). I/R was realized as follows: after laparatomy, a microvascular atraumatic clip was placed across the superior mesenteric artery (SMA) under general anaesthesia, and it was removed after ischemia for 30 minutes. The first dose of melatonin was applied intraperitoneally at the start of reperfusion, The second and third doses were applied intramuscularly on the first and second day. Only SMA dissection under general anaesthesia was carried out in the control group rats. On the third day of the study all the rats were killed, and their bowels were removed. Malondialdehyde (MDA) levels were assayed as an index of lipid peroxidation reflecting free radical reaction in the intestine. Histopathologic analysis was made using light microscopy in a blind fashion. Results: The levels of tissue MDA were found to be significantly lower in groups 3 and 4 compared with group 2 (P > .05). The MDA levels of group 4 did not differ significantly from that of the control group (P > .05). The histopathologic results were consistent with the MDA levels, Conclusion: These results suggest that melatonin has a strong antioxidant effect in preventing intestinal I/R damage, and that this effect is exerted in a dose-dependent manner. J Pediatr Surg 35:1444-1448. Copyright (C) 2000 by W.B. Saunders Company.
17th Annual Meeting of the Turkish-Association-of-Pediatric-Surgeons (TAPS) -- SEP 26-29, 1999 -- ANTALYA, TURKEY
Keywords: intestinal ischemia; ischemia-reperfusion; antioxidant; melatonin